The Impacts of Direct Local Election to The Community Life: Study in Palu, Donggala Regency, and Parigi Mautong Regency - Ani Susanti; Irwan Waris (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This article intends to analyse the impacts of direct elections to the community life. The impacts, in this study, are particularly on political, social, and economic sectors. This research conducted in Palu, Donggala Regency, and Parigi Mautong Regency. The findings of this study were obtained from qualitative research, which the data obtained through qualitative enquiries such as Focus Group Discussion (FGD) which involved some parties who understood, comprehended, and organised the election; in-depth interview to informants, distribute a questionnaire to 162 respondents; do a literature study, and documentary reports. The result of this study shows that the processes of election impact positively to the social and political life of the community but not the economical. Equally important finding is that there are several negative impacts throughout the implementation process of the local elections.